A review and comparison on some rubber elasticity models - Ali, Aidy; Hosseini, Maryam; Sahari, Barkawi (National Institute of Science Communication and Information Resources, 2010)
This study reviews several classical continuum mechanics models for incompressible and isotropic materials based onstrain energy potential and then compares ability of neo-Hookean, Yeoh, Mooney-Rivlin and Ogden models in predicting uniaxialdeformation states based on experimental data from dumb-bell test specimen under uniaxial loading.